Advances in computer science and ubiquitous computing : CSA-CUTE2016 - Park, J. H.; Pan, Yi, 1960-; Yi, Gangman; Loia, Vincenzo, 1961- (Springer, 2017)
This book presents the combined proceedings of the 8th International Conference on Computer Science and its Applications (CSA-16) and the 11st International Conference on Ubiquitous Information Technologies and Applications (CUTE 2016), both held in Bangkok, Thailand, December 19 - 21, 2016. The aim of these two meetings was to promote discussion and interaction among academics, researchers and professionals in the field of ubiquitous computing technologies. These proceedings reflect the state-of-the-art in the development of computational methods, involving theory, algorithm, numerical simulation, error and uncertainty analysis and novel application of new processing techniques in engineering, science, and other disciplines related to ubiquitous computing.
Includes author index.
Keywords: Computer science -- Congresses.; Ubiquitous computing -- Congresses.; elektronické knihy; electronic books